Analysis of Proposed Avtur Rental Rates at Hang Nadim Airport, Batam - Heru Santoso; Ayu Zahra Chandrasari (SAFE-Network, 2024)
Hang Nadim Airport and the infrastructure for providing and distributing aircraft fuel (Fuel Distribution System/FDS) are also reliable. This infrastructure has been built by BP Batam for refueling aircraft operating at Hang Nadim airport. This FDS is in the form of a network of pipes and storage tanks that stretches from Kabil Harbor, Hang Nadim Aircraft Filling Depot (DPPU) to the Hang Nadim airport apron. As the FDS infrastructure developer and area manager as well as a public service agency, BP Batam will determine the value (appraisal) of rental rates for Hang Nadim Airport aviation fuel FDS assets which are the management rights of BP Batam in order to improve services to customers and the community and increase regional competitiveness in accordance with the main tasks and its function.